Construction of Tourism Management Engineering Based on Data Mining Technology - Zhichen Ma (Journal of Electrical and Computer Engineering)
In order to improve the construction quality of tourism management projects, this paper applies data mining algorithm to tourism management, and analyzes the SMOTE algorithm. According to the improvement direction, this paper proposes two improved algorithms, KM-SMOTE and RM-SMOTE, and uses the clustering algorithm to preprocess the minority data set. Moreover, on this basis, this paper establishes clusters and obtains cluster centers. The deficiencies of fuzzy positive and negative class boundaries can be effectively solved by oversampling with the cluster center as the base point, and in the case of appropriately expanding the reasonable data interpolation method, the area space of boundary interpolation can be shrunk, and the performance of the algorithm can be improved. It can be seen from the simulation test research that the tourism management system based on data mining proposed in this paper can play an important role in tourism management and effectively promote the improvement of tourism management efficiency.